The Relationship Between Body Massage and Fatigue Patiens in The Hemodialysis Ward of Royal Prima Hospital 2025 - Zebua, Yohana Agnes; Dakhi, Ribka Juntri Yanti; Situmeang, Foibe Kristin Br; Fitri, Bella Sakina; Lestari, Rindu Hari; Kaban, Karmila Br (Jurnal Ners, 2025)
Patients undergoing hemodialysis therapy often experience fatigue, which can reduce physical ability and lower overall quality of life, as chronic kidney disease (CKD) is characterized by a gradual and irreversible deterioration in kidney function. Body massage is one of the many non-pharmacological treatments that is known to be successful in enhancing blood circulation and having a calming impact, which helps lower levels of weariness. The purpose of this study is to determine whether body massage might lessen fatigue in CKD patients receiving hemodialysis at Royal Prima General Hospital in Medan in 2025. In this study, two groups (intervention and control) were subjected to a pre-test and post-test using a quasi-experimental methodology. Using a saturation sampling technique, 50 respondents from the intervention group and 50 from the control group made up the sample of 100 respondents. The weariness Assessment Scale (FAS) was used to gauge the degree of weariness, and the Wilcoxon Signed-Rank Test was used to evaluate the results. Fatigue levels significantly decreased following the intervention, according to statistical analysis (p=0.000; p<0.05). These results show that regular body massage helps CKD patients receiving hemodialysis feel less exhausted. Therefore, for CKD patients receiving hemodialysis, body massage is advised as an additional therapy.